2014
DOI: 10.7465/jkdi.2014.25.2.293
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents' child abuse, school violence and friends attachment on mental health in childhood

Abstract: A child's mental health is an important element of his proper emotional development. Abuse of children by parents and peer groups are causes of depression and anxiety in children. These conditions become obstacles to their normal growth process which can be a contributing factor to juvenile delinquency. This study is based in the theoretical background of the relationship between abuse from parents and peer groups and children's emotional health. This information is analyzed through structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Previous studies have shown that childhood maltreatment can damage social emotions, such as by making them more irritable, anxious, and depressed (9, 10). In addition, childhood maltreatment can also affect interpersonal relationships (11, 12), even leading to debilitating mental symptoms, such as post-traumatic stress disorder (PTSD) (13). Many studies have found a significant and positive correlation between childhood maltreatment and mental symptoms (1416); this study further explores the specific mediating mechanisms between these two variables by using operable variables as mediating variables.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that childhood maltreatment can damage social emotions, such as by making them more irritable, anxious, and depressed (9, 10). In addition, childhood maltreatment can also affect interpersonal relationships (11, 12), even leading to debilitating mental symptoms, such as post-traumatic stress disorder (PTSD) (13). Many studies have found a significant and positive correlation between childhood maltreatment and mental symptoms (1416); this study further explores the specific mediating mechanisms between these two variables by using operable variables as mediating variables.…”
Section: Introductionmentioning
confidence: 99%
“…이 시기에 가정과 학교에서 생활하며 경험하는 생활 속 의 사건들은 아동, 청소년의 신체적, 심리적 성장과 밀접한 관련이 있다. 특히, 아동, 청소년기에 가정 과 학교환경에서 겪을 수 있는 폭력적 사건은 심리적 건강을 심각하게 해치는 불안, 우울 등의 부정적 정서를 야기하며, 부정적 정서가 지나치면 자살, 폭력 등의 극단적인 행동문제를 야기하기 쉽다 (Min, 2014). 본 연구에서는 가정 및 학교에서의 폭력이 아동, 청소년기의 여학생들에게 미치는 영향력을 종 단자료를 통하여 조사하였다.…”
Section: 이론적 배경unclassified
“…구조방정식모형은 서로 다른 통계분석 방법인 확정적 요인분석 (confirmatory factor analysis)과 다 중회귀분석 (multiple regression analysis) 및 경로분석 (path analysis)을 하나의 통합모형으로 결합시 킨 것으로 볼 수 있다 (Min, 2014). 구조방정식은 잠재변인 간의 구조적인 관계를 설정한 모형을 계량 적으로 관찰한 측정지표 간의 상관행렬계수를 통해 검증하는 통계적인 기법이다.…”
Section: 개인연금 가입에 대한 연구unclassified